Integration of Hypergeometric Superhyperbolic Functions Using Generalized Hypergeometric Function and Its Applications - Paudel, Resham Prasad; Pahari, Narayan Prasad; Basnet, Ganesh Bahadur (The Nepali Mathematical Sciences Report, 2025)
In this article , we explore the properties and relations of the hypergeometric superhyberbolic functions in terms of generalized hypergeometric functions. Then we express the hypergeometric superhyberbolic functions with the help of hypergeometric functions to obtain an integral representation related to classical results within the theory of generalized hypergeometric functions. The work emphasises conditions of convergence, and special cases where the results can be expressed in a simple form and provide a unified framework for evaluating integrals involving hypergeometric functions.